Optimizing Arm Muscle Endurance in Pencak Silat Athletes: Insights from a Literature Review - Nubatonis, Jefrio Demitrimus; Sulistiyono, Sulistiyono; Husein, Muhamad; Septianto, Irvan; Runesi, Salmon; Zakiah, Dwi Manna Nazmi; Dewantara, Julian; Azrina, Jihan; Islam, Syahrizal; Salacup, Vince Louisse D. (Tanjungpura Journal of Coaching Research, 2024)
Background and Study Aim. Pencak Silat is a martial art that demands exceptional physical strength, agility, and endurance. Among these, arm muscle endurance plays an important role in performing effective offensive and defensive maneuvers. Improving arm muscle endurance not only enhances technical efficiency but also minimizes fatigue and prolongs performance during matches. This study aims to explore and analyze proven strategies and methods to optimize arm muscular endurance in Pencak Silat athletes.Materials and Methods. This study used a literature review approach to investigate findings related to improving arm muscular endurance in Pencak Silat athletes. The research process involved a systematic search of electronic databases, including Google Scholar, PubMed, and ScienceDirect, using specific keywords such as “Pencak Silat,” “martial arts,” “arm endurance,” “muscular endurance,” and “training.” After applying exclusion criteria, eight relevant articles were selected for analysis. Additional sources, including university libraries, conference proceedings, and online articles, were also reviewed. The collected data were analyzed qualitatively to identify key themes and effective practices.Results. Some of the key findings in this study include that optimal arm muscle endurance is required by pencak silat athletes to perform repetitive movements such as punches, kicks and locks with maintained speed and power throughout the match. Physiology and Components of Muscular Endurance. Arm muscles have two main endurance components, namely anaerobic endurance (for explosive movements) and aerobic endurance (for long-term endurance). These two components must be drilled in balance to improve the performance of martial arts athletes. Effective Training Methods. Strength training using weights, high-repetition muscular endurance training, and high-intensity interval training (HIIT) have been shown to be effective in improving arm muscle capacity.Conclusion. Optimizing arm muscle endurance is one of the important aspects in improving the performance of Pencak Silat athletes. Well-developed arm muscle endurance allows athletes to maintain their strength and technique during prolonged and intense training or competition. This study highlights the importance of incorporating a balanced and targeted training program to maximize athletes' potential and support their success in Pencak Silat. By synthesizing insights from existing literature, this study seeks to provide clear and practical recommendations for designing effective training programs tailored to the needs of athletes.